Penerapan Metode Course Riview Horay Terhadap Hasil Belajar Siswa IPS Kelas VIII SMP Negeri 2 Kalidawir Kabupaten Tulungagung - Lailatul Fitria; Jani Jani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This research is based on the rapid development of the times which has reduced students' interest in learning, especially in social studies subjects. Therefore, in developing interest in learning, it is necessary to update the learning model. For that, it can be underlined about the expected learning process, namely that during learning students are able to be active. With this, the research contains the application of the course review horay method to student learning outcomes. The method used is a qualitative approach, the type of research is (PTK) Classroom Action Research. There are various stages of research, namely Planning, Implementation, Observation, Reflection. The results after the research was applied were at the beginning of the meeting a Pre-test was held to measure students' understanding of the material on social institutions with the results of student completeness learning as many as an average student score of 77.77, a completeness level of 67%, as many as 18 students completed and 9 students did not complete. And to improve learning outcomes again, 2 Cycles were held with the average score of the Post-test Cycle I, namely the average score increased by 80 and the percentage of completion was 70% with 19 students completing and 8 students not completing, until the assessment results increased in the Post-test Cycle II with an average score of 93.66 and a completion score of 93% until 25 students completed and 2 did not complete. Because the completion of student learning outcomes has reached 93%, the cycle will be stopped. From the results that have been obtained, it can be concluded that the Application of the Course Review Horay method can improve the learning outcomes of class VIII students of SMP Negeri 2 Kalidawir, Tulungagung Regency.